Chemical Constituents of Oxytropis ochrocephala - Guoli Li; Zhengyu Liu; Jiacheng Xie; Yunao Jin; Lei Wang; Hongying Yang; Yilin He; Tong Shen (Molecules, 2025)
A new lignan (1) and a new phenolic glycoside (2), together with eighteen known compounds (3–20), were isolated from Oxytropis ochrocephala. Their structures were unambiguously elucidated by spectroscopic techniques (UV, IR, 1D and 2D NMR), and HR-ESI-MS analysis, as well as by comparison with the literature. The insecticidal activity of these compounds was evaluated against Tetranychus urticae Koch, and the results showed that compounds 3, 9, 15, and 16 had a weak inhibitory effect at a concentration of 1 mg/mL after treatment for 24 h.